On the morphology and possible function of two putative vibroacoustic mechanisms in derbid planthoppers (Hemiptera: Fulgoromorpha: Derbidae). (September 2019) - Davranoglou, Leonidas-Romanos; Mortimer, Beth; Taylor, Graham K.; Malenovský, Igor
Abstract: A mechanism involving interaction of the metathoracic wing and third abdominal segment of derbid planthoppers was first discovered over a century ago, and interpreted as a stridulatory organ for sound production. Although referred to occasionally in later taxonomic works, the detailed morphology, systematic distribution, and behavioural significance of this structure have remained unknown, and its proposed use in sound production has never been corroborated. Here we examine the distribution and morphology of the supposed stridulatory organ of Derbidae and the recently-described vibratory mechanism of planthoppers – the snapping organ, across 168 species covering the entire taxonomic spectrum of the family. We find that many derbids possess snapping organs morphologically similar to those of other planthoppers, and find no evidence for the presence of tymbal organs, which were previously thought to generate vibrational signals in derbids. We find the supposed stridulatory mechanism to be widespread in Derbidae, and conclude that it provides several systematically and taxonomically important characters. Nevertheless, its morphology appears unsuitable for the production of sound, and we instead speculate that the mechanism plays a role in spreading chemical secretions or wax. Finally, we observe wax production by tergal glands in derbid larvae, and illustrate their external morphology in adults. Highlights: Supposed stridulatory organs are widespread in Derbidae. Their morphology does not appear well adapted to producing sound. Many derbids possess snapping organs, but we found no tymbal-like organs. Tergal glands produce wax filaments in some derbid larvae.